Efficiency of banks and municipal funds in Perú, an application of data envelope analysis, for the period 2003 -2022. - Ureña – López, Ficherd Fredy (Universidad Francisco de Paula Santander, 2024)
A longitudinal study was carried out to evaluate the efficiency of Municipal Savings Banks and Savings Banks in the field of loans to microenterprises in the period 2003 to 2022, using the Data Envelopment Analysis (DEA). The sample was made up of 19 financial entities that operated in the analysis interval. For the Data Envelopment Analysis, input variables are considered, which imitate the Coub Douglas Production Function, namely, number of offices and number of personnel of each institution. As a result, it was found that the Banks are more efficient than the Municipal Savings Banks, increasing their efficiency in recent years, while the Municipal Savings Banks showed a similar efficiency with a constant downward trend. Finally, a Multiple Linear Regression Model was estimated to determine the factors associated with Operating efficiency, finding a 5% significance, that the logarithm of the calculated efficiencies is influenced by the return on equity, intermediation ratio (credit per deposit ), type of entity and year of study.